Origami architecture : papercraft models of the world's most famous buildings - Yee (North Clarendon, VT : Tuttle Publishing, 2011)
"CD ROM with templates for cutting Folds flat!"-- | "With this book, some card stock paper, and a hobby knife, you can build spectacular recreations of the most famous buildings in the world. It gives instructions and templates for 16 buildings, including the Parthenon, the White House, the Eiffel Tower, the Chrysler building, and the Forbidden City. There are over 900 photographs detailing the cutting and assembling of the pieces without using glue or tape, except for attaching it to its base. Once the structure is attached to the base not only will it look amazing, but it can be folded up and taken anywhere. For the would be architect, the papercraft hobbyist, or a model builder, Origami Architecture will provide hours of activity and an impressive result"--
Introduction -- The Arc de triomophe (Paris France) -- The leaning tower of Pisa (Pisa Italy) -- The hall of Supreme Harmony (The Forbidden City,Beijing, China) -- The white house (Washington D.C., U.S.A) -- The National center for the performing arts ( Beijing, China) -- Sydney opera house (Sydney, Australia) -- The Eiffel tower (Paris, France) -- Osaka castle (Osaka, Japan) -- Petronas tower (Kuala Lumpur, Malaysia) -- Westminister Abbey (London, England) -- The tower bridge (London, England) -- The United States capitol building (Washington D.C, U.S.A) -- The Chrysker Building (New York, USA) -- The Parthenon (Athens. Greece) -- The Lincoln memorial (Washington D.C., USA) -- Westminster Palace (London, England).
Keywords: ORIGAMI